DEVELOPMENT OF THE AUTHENTICITY OF TRI EKA BUANA VILLAGE AS A TOURISM ATTRACTION - I Made Darma Oka; I Gusti Agung Putu Sri Mahadewi; Ni Gst Nym Suci Murni (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
This study aims to examine the potential for developing the authenticity of Tri Eka Buana Village as a tourist attraction. Research uses qualitative data. Data collection was carried out by observation, interview, and literature study. Informants were taken from community leaders who understood the implications of tourism development using a purposive sampling technique. Data were analyzed by descriptive qualitative. The results show that this village has authentic potential in the form of natural and cultural tourist attractions that can be developed into tourist attractions. The authenticity that is owned consists of 3 categories, namely: objective authenticity, constructed authenticity and existential authenticity. The objective authenticity possessed is in the form of natural tourist attractions such as: Bukit Abah, Dukuh Sakti Waterfall, Puncak Luhur Bukit Abah Temple, and Tirta Danu Seliwah. Constructed authenticity in the form of exotic traditional culture in the form of the Umananing Malini Dance. Existential authenticity, namely the traditional drink of Balinese Arak, which is useful as a means of prayer for Hindus. For this reason, the authentic potential that is owned must be maintained, preserved, and developed by the local community as a competitive advantage for tourism villages so that they can compete competitively. It is recommended to the manager, in the effort to develop authenticity, this can be done by: packaging tourist attractions as special interest-based attractions based on nature and culture, highlighting their beauty, uniqueness and authenticity; presents educational tourism based on nature and culture; involve the community professionally in the management of community-based tourism so as to increase the sense of belonging to caring for a tourist village